2020
DOI: 10.1017/ice.2020.15
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired in name only: A cluster of carbapenem-resistantAcinetobacter baumanniiin a burn intensive care unit and beyond

Abstract: Objective:To describe an investigation into 5 clinical cases of carbapenem-resistant Acinetobacter baumannii (CRAB).Design:Epidemiological investigation supplemented by whole-genome sequencing (WGS) of clinical and environmental isolates.Setting:A tertiary-care academic health center in Boston, Massachusetts.Patients or participants:Individuals identified with CRAB clinical infections.Methods:A detailed review of patient demographic and clinical data was conducted. Clinical isolates underwent phenotypic antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Similarly, Salehi et al (2018) and Raro et al (2017) analyzed the isolates of A. baumannii from patients, staff, and the environment, and emphasized the circulation of CRAB as a nosocomial pathogen in different wards of hospitals, particularly in ICUs. Shenoy et al also identified highly contaminated areas and confirmed the role of environmental reservoirs by investigating five clinical CRAB infection cases (Shenoy et al, 2020). It should be noted that although environmental contamination of CRAB in ICUs has gained increasing attention, research about whether specific clone was responsible for both environmental colonization and ICU infections is still lacking.…”
Section: Environmental Contamination Of Crab In Icusmentioning
confidence: 91%
“…Similarly, Salehi et al (2018) and Raro et al (2017) analyzed the isolates of A. baumannii from patients, staff, and the environment, and emphasized the circulation of CRAB as a nosocomial pathogen in different wards of hospitals, particularly in ICUs. Shenoy et al also identified highly contaminated areas and confirmed the role of environmental reservoirs by investigating five clinical CRAB infection cases (Shenoy et al, 2020). It should be noted that although environmental contamination of CRAB in ICUs has gained increasing attention, research about whether specific clone was responsible for both environmental colonization and ICU infections is still lacking.…”
Section: Environmental Contamination Of Crab In Icusmentioning
confidence: 91%
“…This situation, in a country where CRAB prevalence is reported to be highest globally, 28 is in stark contrast to those described in monoclonal outbreaks in hospitals in low-prevalence high-income countries. 4,79 The prevalence of CRAB in the ICU was also found to be higher than previously appreciated, likely owing to our environmental screening.…”
Section: Discussionmentioning
confidence: 57%
“…Recent studies have demonstrated the utility of whole-genome sequencing (WGS) for high-resolution characterisation of such single-centre outbreaks or populations. 4,[8][9][10] Endemic hospital A. baumannii populations, however, can be composed of multiple phylogenetic clusters. 11,12 WGS has been employed to assess multi-centre CRAB populations, revealing that individual hospitals harbour multiple clusters and that these may be found across multiple hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…WGS of isolates from a suspected outbreak allows for determination of clonality, correlation with regional and national data, and establishment of transmission timelines. 21 , 22 , 23 , 24 Although other methods exist for determining isolate clonality (eg, pulsed-field gel electrophoresis), only WGS also identifies ARGs and virulence genes, and finely resolves degrees of relatedness. 23 , 25 , 26 WGS is also the preferred method for fungal genotyping in outbreak investigations, because many of these pathogens lack a preexisting typing scheme.…”
Section: Whole-genome Sequencing Of Cultured Isolatesmentioning
confidence: 99%